Molecular Organosulphur, Organoselenium and Organotellurium Complexes as Homogeneous Transition Metal Catalytic Systems for Suzuki Coupling. Issue 33 (1st September 2022) - Arora, Aayushi; Oswal, Preeti; Sharma, Deepali; Tyagi, Anupma; Purohit, Suraj; Sharma, Pankaj; Kumar, Arun
Abstract: During last two decades, researchers have employed organochalcogen compounds as ligands for the development of pre‐formed chalcogen ligated molecular complexes. During 2013–2020, various chalcogen containing homogenous catalytic systems for Suzuki Miyaura cross‐coupling reaction have been synthesized. The review provides insights into the synthetic methodologies for the preparation of organochalcogen ligands and their transition metal complexes. Another central aspect discussed is the application of such catalytic systems in Suzuki Miyaura coupling. Rationalization about the effect of temperature, substrate scope, organoborane derivatives and aryl halides employed has been elaborated. Effect of binding mode, ligand framework, chalcogen donor atom, metal and many other aspects that influence the catalytic potential of various systems have also been covered. Various other aspects such as green catalysis, use of non‐conventional energy sources have also been analyzed. Abstract : Synthetic methodologies for catalytically relevant organosulphur, organoselenium, and organotellurium ligands and their transition metal complexes are highlighted. Applications of such complexes in homogeneous catalysis for Suzuki coupling of aryl halides with arylboronic acid are critically analysed. The effect and advantage of the presence of S or Se or Te donor have been rationalized.